Medindo a velocidade do som utilizando figuras de Lissajous - MAGNO, Fátima Nazaré Baraúna (Universidade Federal do Pará, 2017)
There are several techniques to obtain the sound velocity in air, from the very simple ones, which use the relation between distances and time, until the more sophisticated ones, associated with oscillatory phenomena. In this work we propose an experimental aparathus which involves the Lissajous figures and ressonance tubes. The physical phenomena that appear in the process allow the student to observe and understand several ondulatory processes, as well as the superposition principle and can be applied to engenier and physics undergraduate students.